Influence of stratified charge organized by double injection strategy on combustion and emissions on an EGR diluted GDI engine. (25th July 2019) - Feng, Shuang; Hong, Wei; Xie, Fangxi; Yang, Ye; Su, Yan; Li, Xiaoping
Highlights: Effects of stratified charge on combustion and emissions on a GDI engine. Three mixture methods were used in the whole test. SMM 9:1 method can improve the engine combustion characteristics. The fuel consumption of SMM 9:1 is the lowest when the EGR ratio was 20%. SMM 8:2 method can weaken the engine combustion performance at the higher ratios. Abstract: The paper reports an experiment about stratified charge organized by double injection strategy aimed to improve GDI engine performance with stoichiometric mixture under EGR dilution, the whole test used three mixture methods, their combustion and emissions characteristics were compared. The results indicated that when the engine speed was 1400 rpm and fuel consumption was 1.95 kg/h, the flame development, combustion duration and variation of stratified mixture method (SMM) with the first and second injection proportion of 9:1 reduced obviously compared to HMM method at the same EGR dilution level. When the EGR ratio was 20%, the engine obtained the lowest fuel consumption, meanwhile, compared with HMM method, the brake specific fuel consumption (BSFC) of SMM 9:1 was reduced by 1.55% and achieved lower NOx emissions. However, when the injection proportion changed to 8:2, the improvement of flame development and combustion duration weakened, the combustion variations and incomplete combustion even increased at the higher EGR ratios (≥20%), the BSFC, particle number and CO emissions were deteriorated than HMM method. Overall, the engine combustion and performance can be improved by stratified mixture with EGR dilution, but injection proportion must be adjusted optimally, it was better at 9:1 in the test.